IDENTIFICATION OF ENVIRONMENTAL FACTORS AFFECTING THE RACINGPERFORMANCE OF RACE CAMELS IN THE UNITED ARAB EMIRATES - Al-Shorepy, Salih Salih (Emirates Journal of Food and Agriculture, 2011)
The aim of the present study was to investigate environmental factors affecting the racing performance of race camels in the United Arab Emirates (UAE). The traits evaluated were racing time and race speed. The data used in this study were obtained from UAE Camel Race Association. One hundred ninety races of varying distances with 50 camels per race were video recorded for which the first ten winners were determined. The analyses were conducted using three statistical linear models. Age, sex, breed, sex by breed and distance effects were included in the linear models. In each race, three groups were considered; fastest ten, fastest three and the fastest. Average speed of race camels in UAE was 10.6 m/s (SD=0.26; range: 9.20-11.79 m/s), with coefficient of variation of 1.99 percent. Camels with 3 years of age were significantly (P < 0.05) faster than the other age groups for fastest three. Except for camels with 5 years of age, females were significantly (P <0.05) superior to males for the fastest ten. Both race speed and racing time were not affecting by the breed for fastest three and the fastest. The sex by breed interaction had no significant effects on both race speed and racing times.